Seasonal modulation of diurnal food consumption in Indian songbirds. Issue 4 (3rd July 2016) - Das, Samya; Gupta, Neelu Jain
Abstract: Seasonal changes in daily food consumption have a direct bearing with energy requirement of bird that is in turn associated with life history stage of birds. We compared seasonal changes in daily food intake in adult male migratory redheaded bunting ( Emberiza bruniceps ) that over winters in Indian subcontinent with those in non-migratory blackheaded munia to reiterate the same. We also compared daily food eating pattern (DFEP) in wintering blackheaded and redheaded buntings, closely related Emberizidae finches to establish circadian nature of feeding behavior and how it varied at species level. The birds were held under short days (8L:16D; 8 h of light and 16 h of darkness) and two hourly food consumption was measured to profile their DFEP. Further, we extended the study to establish how the circadian pattern of food consumption varied depending on birds' physiological state and effect of photoperiod in adult male redheaded buntings. Redheaded buntings DFEP and locomotor activity were compared in pre-migratory months of February (spring) and September (autumn). The results suggest that September (photorefractory) birds exhibit clear bimodality in their feeding behavior as compared to (photosensitive) birds in February. Another experiment compared bird's DFEP held under short (8L:16D) and long (16L:8D) days for 5 weeks and suggested that under long days, prolonged hours of photophase render adaptive advantage to birds for positive energy budgeting. The present study clearly establishes the circadian nature of feeding behavior and that it modulates over seasons. The bimodal i.e. morning and evening peaks of food consumption suggest morning–evening food entrainable oscillators, however this needs to be investigated with mechanistic approach in future studies.